Effect of Carbon Dioxide (CO2)-Rich Water Immersion on Changes of Peripheral Blood Flow in Patients with Kidney Disease - Yammar Yammar; Annisa Suwahru; Andi Rizky Arbaim Hasyar; Irfan Idris; Irawan Yusuf; Haerani Rasyid (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Endothelial dysfunction is experienced in hemodialysis patients, characterized by stiffness in the blood vessel walls resulting in decreased peripheral blood flow. The research objective was to determine the effect of immersion in CO2 water on peripheral blood flow changes. Experimental design with 30 patients divided into two groups; 18 patients immersed their feet in CO2 water (1,300 ppm) at 37-38°C and 12 patients were immersed in fresh water at 36-37°C performed 2-3 times per week for four weeks, measurement of peripheral blood flow using Laser Doppler Flowmetry on day 1 and 28. Peripheral blood flow from the CO2 water immersion group decreased from 12,443 mL/minute to 11,677 mL/minute (decreased by 0.766 mL/minute), while the freshwater immersion group decreased from 8,471 mL/minute to 6,776 mL/minute (decreased by 1,695 mL/min). Immersion in CO2 water tends to reduce peripheral blood flow inhibition more than immersion in fresh water in hemodialysis patients.